A84 Collisions between pedal cyclists and heavy vehicles: an in depth analysis of fatalities in London. Issue 2 (June 2015) - Christie, Nicola; Talbot, Rachel; Reed, Steve; Thomas, Peter
Abstract: Background: Cycling is promoted in London to improve health and encourage more sustainable travel. However, the perceived safety of cycling is a major reason given by people not to cycle. Despites people's concerns about the safety of cycling relatively few cyclists are injured and therefore there is limited information about the factors that contribute to their collisions. However, because of their severity, fatal collisions are subject to in-depth investigation by the police and provide an opportunity to learn more about causal factors. In London between 2007–2011 there were 79 fatal and life threatening collisions involving cyclists of which 53 were available for analysis. Over half of these fatal collisions involved heavy goods vehicles, large vans and buses. This paper presents findings of a systematic analysis of collisions involving cyclists and large, heavy vehicles focusing on the interaction between road users, infrastructure and vehicle characteristics and the implications for countermeasures. Methods: The study involved a case review of 53 pedal cycle fatalities in London. The method involved six stages: Formation of the expert research group Data retrieval Protocol development (check with stakeholder group for completeness of data sources) Case collection and quality control (develop coding glossary) Case reviews and countermeasure development Linking countermeasure development to evidence of effectiveness Results: The most common characteristics of the infrastructure associated with fatal collisions involving bicycles and heavy vehicles were the lack of integration of cycling facilities with the wider traffic environment and road narrowing. These characteristics created conflict points between cyclists and other vehicles. The most common vehicle characteristics associated with collisions were related to the driver's vision of the cyclist and the cyclist being dragged under the wheels of vehicle. The most common characteristics of road user behaviour associated with collisions were the positioning of the cyclist in relation to vehicle where the cyclist typically moved forward to the left side of the truck whilst it was stationary or moving into position at a junction. This placed the cyclist in a zone of potential conflict with the vehicle where it was inherently more difficult for the truck driver to see the cyclist. Conclusions: There is a paucity of evidence on the effectiveness on countermeasures to reduce collisions between cyclists and truck drivers. This study suggests that countermeasures should focus on reducing conflict points between road users, improving truck drivers vision of cyclists and training drivers and cyclists with regard to positioning especially at junctions.